Molecular identification of toxigenic Aspergillus and Fusarium species isolated from traditional cheese wagashi produced in Benin. - SESSOU, PHILIPPE; MISSIHOUN, ANTOINE ABEL HOUMÈNOU; AGBANGLA, CLÉMENT (My University, 2018)
Traditional cheese wagashi is an important source of animal proteins of excellent nutritional values mainly for low income populations in Benin. It’s often used in replacement of meat and fish in different dishes. Despite its importance, wagashi can be contaminated by various toxigenic mould strains capable of producing mycotoxins with advert effects on consumers’ health. It is therefore, necessary to provide a clear picture of the potentially toxigenic mould strains that colonizes wagashi. The study aimed to identify toxigenic Aspergillus and Fusarium species isolated from traditional cheese wagashi produced in Benin in order to assess the associated health risks to consumers. Preliminary isolation and identification of seven toxigenic mould isolates were carried out using conventional microbiological, macroscopic and stereomicroscopic methods. The isolates were further confirmed by PCR using species specific primers. The study revealed that four of the seven isolates namely Aspergillus flavus, A. ochraceus, Fusarium verticallioides, F. poae previously identified by conventional methods were confirmed by PCR. These results showed the limits of conventional methods in microbial identification and revealed that wagashi produced in Benin contains toxigenic strains of moulds that can affect its safety with risks of hazardous mycotoxins ingestion by consumers.
Keywords: Toxigenic moulds; Mycotoxins; Wagashi; Molecular identification; Benin.